Regulation of Host Innate Immunity by Non-Coding RNAs During Dengue Virus Infection - Rajput, Roopali; Sharma, Jitender; Nair, Mahima T.; Khanna, Madhu; Arora, Pooja; Sood, Vikas (Frontiers in Cellular and Infection Microbiology, 2020)
An estimated 3.9 billion individuals in 128 nations (about 40% of global population) are at risk of acquiring dengue virus infection. About 390 million cases of dengue are reported each year with higher prevalence in the developing world. A recent modelling-based report suggested that half of the population across the globe is at risk of dengue virus infection. In any given dengue outbreak, a percentage of infected population develops severe clinical manifestations, and this remains one of the “unsolved conundrums in dengue pathogenesis”. Although, host immunity and virus serotypes are known to modulate the infection, there are still certain underlying factors that play important roles in modulating dengue pathogenesis. Advanced genomics-based technologies have led to identification of regulatory roles of non-coding RNAs. Accumulating evidence strongly suggests that viruses and their hosts employ non-coding RNAs to modulate the outcome of infection in their own favor. The foremost ones seem to be the cellular microRNAs (miRNAs). Being the post-transcriptional regulators, miRNAs can be regarded as direct switches capable of turning “on” or “off” the viral replication process. Recently, role of long non-coding RNAs (lncRNAs) in modulating viral infections via interferon dependent or independent signaling has been recognized. Hence, we attempt to identify the ‘under-dog’, the non-coding RNA regulators of dengue virus infection. Such essential knowledge will enhance the understanding of dengue virus infection in holistic manner, by exposing the specific molecular targets for development of novel prophylactic, therapeutic or diagnostic strategies.